Fundamental analysis on the intentional use of nonlinear stiffness in some dynamical systems - Gatti, Gianluca; Brennan, Michael J. [UNESP]; Tang, Bin (Springer Nature, 2019)
Although nonlinearity in dynamical systems have been of concern for many years due to its unpredictable effects, researchers and engineers have recently begun to incorporate it into mechanical and mechatronic devices to improve their performance, make them compact and reduce their weight. This paper presents some applications where geometrical nonlinear stiffness is adopted to beneficial use. Vibration energy harvesters, isolators and micro devices for flight are considered, and the advantages of incorporating nonlinearity is emphasized. A fundamental investigation is conducted on a simple model of nonlinear oscillator consisting of linear springs specifically arranged.
Keywords: Energy harvesting; Nonlinear vibration; Stiffness nonlinearity; Vibration isolation